Protection of renal function by green tea extract during Plasmodium berghei infection - Somsak V. (2014)
Impairment of renal function from oxidative stress during malaria infection is one of the leading causes of death in endemic areas. Since blood urea nitrogen and creatinine levels in plasma can be used as markers for monitoring renal damage, this study investigated the effect of green tea extract on reduction of blood urea nitrogen and creatinine levels during malaria infection using Plasmodium berghei ANKA infected mice as in vivo model. For in vivo testing, ICR mice were infected with 1×107 parasitized erythrocytes and green tea extract was subsequently administered orally twice a day for 10 consecutive days. Parasitemia was estimated by standard microscopy, and blood urea nitrogen and creatinine levels in plasma were also measured. It was found that parasitemia kept increasing until animal death, and is strongly correlated with high blood urea nitrogen and creatinine. The highest levels of blood urea nitrogen and creatinine in plasma were found on day 10 after infection. However, blood urea nitrogen and creatinine levels in plasma were reduced and decreased significantly (p<0.01) in green tea extract treated mice, compared with untreated group. It can be concluded that green tea extract can protect and maintain renal function during malaria infection, and this extract can be developed for use as a supplement and combination therapy. © 2013 Elsevier Ireland Ltd.